GEMOLOGICAL LAW OF UKRAINE: FORMATION PROBLEMS AND DEVELOPMENT PROSPECTS - Kirin, R.; Baranov, P.; Koziakov, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article analyzes the scientific and legislative provisions connected with the specifity of the legal regulation of relations in the field of gemological activity and gemological objects. The current state of sources of gemological law and their belonging are investigated, which is nowadays ambiguous, since they get to a system of currency law (a component of financial and credit or budgetary and financial legislation) as well as to a system of industrial legislation, while having the provisions of mining, economic, civil, administrative, fiscal, customs and expert legislation in the contents. It is proposed to consider gemological law as a set of legal norms regulating public relations in the field of organizing and carrying out gemological activities connected with the acquisition of the right to use, mining, property, use and operations with gemological objects in the form of subsoil, mineral, production and secondary resources, control over their turnover and expertise. It is noted that consideration of precious stones and precious metals, having geological and mineralogical, physicochemical, jewellery and industrial, and legal differences, as the complex object in the context of the domain of the unified legislative act, intended to be a basis of new market relations in the field of jewellery transactions, could be regarded as the justified one only at the early stage of legislative base formation for the field. Provisions are given, according to which it is recognized that the current law is outdated, since its subject of regulation has been transferred mainly to the subordinate level; the mechanisms for replenishing state funds provided in it are contradictory, incomplete and practically not implemented in practice; the form of restrictions in the circulation of valuable objects and their validity are debatable; relations of the quality and safety of products, consumer protection, ensuring a balance of public and private interests, equality of business entities, competitiveness of the industry need updating in European integration legal regulation. For the first time in the context of geological and legislative science, the authors propose to form a structure of the gemological law system based upon the principles of differentiation of a type of gemologically important activities for generic derivatives (i.e. gemological and resource law; right of gemological circulation; right of gemological expertise etc.) as well as a type of gemological objects and resources for direct groups. Development prospects of gemological legislation are connected with its reduction to a certain agreed system and its unity provision by means of the internal and external improvement of contents and development of the Gemological Code of Ukraine.
Keywords: gemological legislation; precious stones; circulation of precious stones; gemological resources; gemological activities